Effect of the ZrO2 phase on the structure and behavior of supported Cu catalysts for ethanol conversion - Sato, A.G.; Volanti, D.P.; Meira, D.M.; Damyanova, S.; Longo, E.; Bueno, J.M.C. (Journal of catalysis, 2013)
Effect of ZrO2 phases on the formation of acetaldehyde and ethyl acetate from ethanol over Cu/ZrO2 catalysts. [Display omitted] •Cu catalysts supported on am-, m-, and t-ZrO2 for selective ethanol conversion.•Cu/m-ZrO2 catalyst shows a high selectivity to ethyl acetate.•The high rate of ethyl acetate is defined by oxygen mobility from bulk ZrO2 to Cu.•A high rate for acetaldehyde formation is observed for Cu/t-ZrO2 catalyst. The effect of amorphous (am-), monoclinic (m-), and tetragonal (t-) ZrO2 phase on the physicochemical and catalytic properties of supported Cu catalysts for ethanol conversion was studied. The electronic parameters of Cu/ZrO2 were determined by in situ XAS, and the surface properties of Cu/ZrO2 were defined by XPS and DRIFTS of CO-adsorbed. The results demonstrated that the kind of ZrO2 phase plays a key role in the determination of structure and catalytic properties of Cu/ZrO2 catalysts predetermined by the interface at Cu/ZrO2. The electron transfer between support and Cu surface, caused by the oxygen vacancies at m-ZrO2 and am-ZrO2, is responsible for the active sites for acetaldehyde and ethyl acetate formation. The highest selectivity to ethyl acetate for Cu/m-ZrO2 catalyst up to 513K was caused by the optimal ratio of Cu0/Cu+ species and the high density of basic sites (O2−) associated with the oxygen mobility from the bulk m-ZrO2.